2009
DOI: 10.1080/00016340902846064
|View full text |Cite
|
Sign up to set email alerts
|

Validation of epithelial ovarian cancer and fallopian tube cancer and ovarian borderline tumor data in the Danish Gynecological Cancer Database

Abstract: The validity of ovarian cancer data in the DGCD is sufficient for quality monitoring in gynecological oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Reporting to the DGCD is compulsory for all gynecological, pathological, and oncological departments in Denmark who are participating in the diagnosis and treatment of these cancers. 6 Lifelong follow-up of cases is possible through linkage via personal identification number to the Danish Hospital Discharge register, which contains data on death and discharge diagnoses among others.…”
Section: The Danish Gynaecological Cancer Databasementioning
confidence: 99%
“…Reporting to the DGCD is compulsory for all gynecological, pathological, and oncological departments in Denmark who are participating in the diagnosis and treatment of these cancers. 6 Lifelong follow-up of cases is possible through linkage via personal identification number to the Danish Hospital Discharge register, which contains data on death and discharge diagnoses among others.…”
Section: The Danish Gynaecological Cancer Databasementioning
confidence: 99%
“…The study is based on prospectively collected data from DGCD, which holds information on 97% of Danish patients diagnosed with ovarian cancer since January 1st, 2005 [5]. The pathologists have special focus on discriminating between peritoneal, ovarian and fallopian tube involvement and origin.…”
Section: Danish Gynecological Cancer Database (Dgcd)mentioning
confidence: 99%
“…For each patient, data are collected on surgical, pathological, and oncological variables. A validation study found 94% of cases to be covered in the database, and surgical and pathological data to be sufficient for research [14]. However, oncological data are incomplete since some oncological departments have not had the resources to fill the forms in the database [15].…”
Section: Data Sourcesmentioning
confidence: 99%